Enrichment of Tropical Peat with Micronutrients for Agricultural Applications: Evaluation of Adsorption and Desorption Processes - Melo, Camila de A. [UNESP]; Oliveira, Lilian K. de [UNESP]; Goveia, Danielle [UNESP]; Fraceto, Leonardo F. [UNESP]; Rosa, Andre H. [UNESP] (Soc Brasileira Quimica, 2014)
The objective of this work was to evaluate the adsorption and desorption of micronutrients in tropical peats, from the perspective of potential agricultural applications. Adsorption experiments were performed at different pH values, using solutions containing individual and multiple metal ions. Maximum adsorption capacity occurred at pH 6.0, and the order of affinity was Cu > Fe > Co > Ni > Zn = Mn. Release of the micronutrients was evaluated at different pH values, using an aqueous medium as well as soil and plants. Release of the micronutrients was most efficient at pH 6.0, and followed the order: Fe > Zn > Mn > Co = Ni > Cu. Micronutrient release to the soil was accompanied by uptake by the plant. The use of tropical peat enriched with micronutrients could contribute to improved agricultural productivity, since the release profile of the micronutrients can effectively stimulate plant growth.
Keywords: adsorption; desorption; micronutrients; peat; plant growth